Microscopic electroelastic modeling of a spin transition with symmetry breaking - Slimani, Ahmed (2021)
A theoretical approach combining Monte-Carlo and molecular-dynamics techniques is developed to deal with the structural anisotropy upon the spin transition in molecular materials. The simulations were done on a 2D lattice, where the cells have two structural symmetries: square-shaped (non-degenerated) at a low spin (LS) state and a diamond-shaped (degenerated) at a high spin (HS) state. We investigated the thermally induced spin transition and the relaxation of a metastable HS state trapped at low temperatures. We demonstrated that the structural parameters have a crucial impact on the spin transition, and by adjusting the lattice and the elastic parameters, we were able to generate a two-step thermally induced spin transition. The analysis of magnetic and structural properties pointed out that the symmetry breaking reduces significantly the cooperativity between the lattice’s cells. The maps of the difference between cell diagonals reveal an auto-organized HS lattice with an alternation of different symmetries over the state, confirming the symmetry breaking when switching from an LS to HS state. The mechanical relaxation of an LS lattice containing HS defects shows an anisotropic distribution of the elastic energy, channelized over the shortest paths toward the borders of the lattice. The interaction between two HS defects placed in a LS lattice is as well investigated as a function of their separating distance for different symmetries of the HS state. We demonstrated that the HS symmetry impacts the HS/LS elastic barrier as well as the dependence of the relaxed elastic energy on the distance separating two HS defects introduced in an LS lattice